2016
DOI: 10.5334/cstp.30
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Life – Quality Assessment of Novice vs. Expert Georeferencers

Abstract: The majority of the world's billions of biodiversity specimens are tucked away in museum cabinets with only minimal, if any, digital records of the information they contain. Global efforts to digitize specimens are underway, yet the scale of the task is daunting. Fortunately, many activities associated with digitization do not require extensive training and could benefit from the involvement of citizen science participants. However, the quality of the data generated in this way is not well understood. With two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Findings from this study confirm and complicate previous recommendations for involving volunteers in natural history digitization projects. Researchers and practitioners have suggested that recruiting volunteers with knowledge of geography and organisms represented in a collection could result in more accurate transcriptions (Ellwood et al 2015;Merckx et al 2018), and that recruiting volunteers through amateur-expert organizations would be one way to connect with individuals who may have such knowledge (Ellwood et al 2016;Merckx et al 2018). This case study provides some evidence that recruiting citizen science volunteers through amateur-expert organizations can lead to the involvement of volunteers with extensive knowledge of local geography.…”
Section: Discontinuity and Handling Boundary Experiences In Citizen Smentioning
confidence: 79%
“…Findings from this study confirm and complicate previous recommendations for involving volunteers in natural history digitization projects. Researchers and practitioners have suggested that recruiting volunteers with knowledge of geography and organisms represented in a collection could result in more accurate transcriptions (Ellwood et al 2015;Merckx et al 2018), and that recruiting volunteers through amateur-expert organizations would be one way to connect with individuals who may have such knowledge (Ellwood et al 2016;Merckx et al 2018). This case study provides some evidence that recruiting citizen science volunteers through amateur-expert organizations can lead to the involvement of volunteers with extensive knowledge of local geography.…”
Section: Discontinuity and Handling Boundary Experiences In Citizen Smentioning
confidence: 79%
“…Almost all specimens arrive in collections with locality data, although collections staff sometimes need to add missing geographic coordinates. Legacy collections often lack coordinates and georeferencing has become a major activity of collections staff who use platforms such as GEOLocate to georeference large numbers of localities (Ellwood et al ., ; Seltmann et al ., ). Having all localities in a collection geo‐referenced should be a goal of all institutions housing natural history collections.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the only study comparing expert-generated geocoordinates and citizen science-generated geocoordinates, using students as a proxy, discussed differences in the georeferencing process used by each group [34]. Citizen scientists tended to measure the distance from a named place to a location of interest as the crow flies as opposed to measuring distance along a road, as performed by the experts, who also found typos in directions, such as east instead of west [34].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the only study comparing expert-generated geocoordinates and citizen science-generated geocoordinates, using students as a proxy, discussed differences in the georeferencing process used by each group [34]. Citizen scientists tended to measure the distance from a named place to a location of interest as the crow flies as opposed to measuring distance along a road, as performed by the experts, who also found typos in directions, such as east instead of west [34]. For the CoGe Arkansas Vascular Flora project, Soteropoulos emphasized the process used by expert georeferencers through realtime georeferencing in a two-hour group training session, reinforced the process through one-on-one training sessions, reiterated the process to answer questions during office hours, and provided citizen scientists with a standard operating procedure to connect the process steps with the CoGe tools (Appendix A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation